El uso de Photovoice en el aula de lenguas extranjeras para promover la autorreflexión y el desarrollo de la comunicación oral - Levi Altstaedter, Laura (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
The present article describes a pedagogical project on the implementation of Photovoice in the Spanish as a foreign language class at an American university. The two main objectives of the project are, on the one hand, to motivate students to investigate concepts related to interculturality, specifically, perspective taking and self-knowledge, through the use of photography as a trigger, and on the other hand, to create a space for the development of oral communication competence in a framework of discussion about authentic topics. This article offers details of the tasks designed as part of the project, as well as a reflection on their relevance to be implemented in the L2 classroom.